2018
DOI: 10.3389/fonc.2017.00324
|View full text |Cite
|
Sign up to set email alerts
|

Planning Today for Tomorrow’s Research: Analysis of Factors Influencing Participation in a Pediatric Cancer Research Biorepository

Abstract: BackgroundBiobanks have become a powerful tool that fosters biomedical research. The success of biobanks depends upon people’s perception and willingness to donate their samples for research. This is the first biorepository in Egypt, hence, little is known about the beliefs and attitudes of parents toward participation.AimTo investigate the level of willingness of Egyptians to donate samples of their children and themselves for research and the different factors influencing participation.Materials and methodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…These results are comparable to those of a previous study, which found that two-thirds of Egyptians surveyed were willing to donate blood samples for future research [27]. In another study, about 97% of Egyptian parents of pediatric cancer patients agreed to donate blood samples for a cancer research biobank [28]. Our results showed similar attitudes towards donating samples for biomedical research to the attitudes of the general public in Germany, [11] Jordan, [10] and Sweden [14].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results are comparable to those of a previous study, which found that two-thirds of Egyptians surveyed were willing to donate blood samples for future research [27]. In another study, about 97% of Egyptian parents of pediatric cancer patients agreed to donate blood samples for a cancer research biobank [28]. Our results showed similar attitudes towards donating samples for biomedical research to the attitudes of the general public in Germany, [11] Jordan, [10] and Sweden [14].…”
Section: Discussionsupporting
confidence: 84%
“…Studies conducted on the effect of sociodemographic data on attitudes towards donating to biobanks have reported contradictory results. For example, while Labib et al [28] and Nilstun and Hermerén [32] have reported negative or restrictive attitudes towards donating samples to biobanks among those with higher levels of education, Ahram et al [10] reported the presence of a positive correlation between higher education and willingness to donate samples for research.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a similar proportion (57.7%) of 315 senior Egyptian medical students studying in medical schools in the same governorates (Cairo, Alexandria, and Assiut), who participated in a similar survey indicated a similar reluctance to donate samples or encourage family members to do so (data not published). Another comparable study to the current work reported a negative correlation between willingness to donate samples to biobanks and higher levels of education [26]. Evidently, some physicians as well as medical students prefer to lead the process of patient care and research, but not to take part in it by donating their own samples.…”
Section: Plos Onesupporting
confidence: 64%
“…Especially, if the research involves invasive procedures drug trial. The parent education level can also influence the decision of participation in paediatric research [26,27].…”
Section: Resultsmentioning
confidence: 99%